Hukum Seputar Risywah dalam Perspektif Hadis Nabi - Muhammad Ikhsan; Azwar Iskandar (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2021)
This study aimed to analyze: (i) the position of hadiths about risywah; (ii) the legal view of the hadiths concerning risywah; (iii) the form of risywah application based on these hadiths; and (iv) the solution of the Prophet's hadiths in eradicating the phenomenon of risywah. This research was qualitative descriptive research with lafzi and thematic methods (mawdlu'i). The results showed several things. First, there are a number of hadiths of the Prophet that generally be used as arguments (legal basis) in discussing risywah and its application in the life of mankind. Second, the hadiths of the Prophet turned out to be the same conclusion that risywah is an act that gets a curse from Allah and becomes a very strong foundation to establish the prohibition of risywah. Third, the hadiths of the Prophet also provide some examples of applications from risywah itself, among others: giving gifts to officials or state officials, giving bribes with the intention of canceling legal processes or provisions, and giving bribes in an effort to escape from an obligation. Fourth, hadiths of the Prophet (s) provide solutions to prevent and eradicate risywah that have proven effective in the prophetic era and also in the era of Khulafa' al-Rasyidun, among others in the form of coaching (tarbiyah) faith in officials and state apparatus, improving the system of supervision and audit of the wealth of officials and authorities, and the determination and imposition of strict sanctions to people who are proven to be involved in risywah.